Zróżnicowanie dochodów budżetów województw samorządowych z tytułu udziałów z podatków stanowiących dochód budżetu państwa w latach 1999-2004 - Ślebocka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main object of the consideration are provinces' revenues as a part of state tax revenues and their regional differentiation in Poland. The analysis' period includes years between 1999 and 2004. The author presents a set of data concerning the provinces' amounts of own revenues and participation sizes in income from state taxes with reference to tasks and macroeconomic changes in the provinces.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 292-309